1917
DOI: 10.1113/expphysiol.1917.sp000224
|View full text |Cite
|
Sign up to set email alerts
|

The Parathyroids:—tetania Parathyreopriva: Its Nature, Cause, and Relations to Idiopathic Tetany. Part I.: Introduction, General Methods, and Symptoms

Abstract: 1. Idiopathic tetany and the various theories as regards its etiology are considered. 2. The previous work upon experimental tetany is dealt with in the three periods— (a) before the recognition of the possible significance of the parathyroid; (b) while the distinction between the thyroids and parathyroids was still doubtful; (c) after the direct implication of the parathyroids in the production of the symptoms had been established. The evidence that the condition is a true tetania parathyreopriva is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1919
1919
1971
1971

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The strongly basic properties of these substances, their reported occurrence in muscle, and in normal human urine, and their reported increase there during abnormal muscular activity (25), suggested that creatine might be undergoing a c-hange into one of these two substances. At the same time, there were a number of serious objections to this view.…”
Section: (2) the Ponsibility Of The Transformation Of Creatine Into Mmentioning
confidence: 99%
“…The strongly basic properties of these substances, their reported occurrence in muscle, and in normal human urine, and their reported increase there during abnormal muscular activity (25), suggested that creatine might be undergoing a c-hange into one of these two substances. At the same time, there were a number of serious objections to this view.…”
Section: (2) the Ponsibility Of The Transformation Of Creatine Into Mmentioning
confidence: 99%
“…Recent years have produced much work, notably that of Noel Paton and Findlay (2) and more recently of Frank Stern and Nathmann(3) and Gy6rgy and Vollmer4 on the experimental production in animals of the symptoms of tetany by parathyreoid removal and by the injection of guanidin and di-methyl guanidin salts. A lowering of the galvanic threshold in a manner strictly similar to that seen in idiopathic tetany is shown to be a constant phenomenon in such conditions experimentally produced.…”
mentioning
confidence: 99%
“…To determine the chronaxie by condenser discharges Lapicque proceeds as follows: (1) the rheobase is found by determining the minimal current which will excite if allowed to run continuously (i.e. for more than half a second); (2) the voltage required for the rheobase is doubled, and a series of condensers is charged to this value. These condensers are now discharged through the tissue and the smallest capacity which will just excite is determined.…”
mentioning
confidence: 99%
“…W. F. KoCH(1) found in the urine of parathyreoidectomiised dogs a number of toxic bases, including guanidin and dimethyl-guanidin, to which he ascribed the symptoms. Noel Paton, Findlay and Watson, in conjunction with Burns and Sharp e (2) independently arrived at the conclusion that guanidin or its methyl derivatives are the toxic agents in tetania parathyreopriva and in idiopathic tetany. B ie d (3,p.…”
mentioning
confidence: 99%